P402 Recognisable patterns to childhood experiences of mind formation. (June 2019) - Kearney, Peter
Abstract : The title deliberately echoes Smith's book on Recognizable Patterns of Human Malformation first published in 1970. Smith's patterns relate to antenatal events, whereas patterns that shape our minds relate to special experiences during childhood. As Paediatricians we are very familiar with incremental formation which we chart by measuring growth and evaluating development. We are less au fait with special experiences that shape our minds probably because Anthropology has been peripheral to medical education. The boundaries of different sciences are blurring as interest in the formation of our minds draws on many disciplines. Our deep interest in biological child health aims to treat and prevent diseases from the newborn to adolescence. Biology is not the whole story. The great status transformations from child to adult and from sickness to health require ritual to establish new orientations in the mind. Childhood experiences of prolonged cancer treatment reverberate into adulthood long after treatment has finished. Adult survivors may remain marginalised from their peers despite support from psycho-social professionals (Larcombe et al, 2002; Stam, 2005). Paediatricians and Psychologists largely rely on the research methods of objective science, but their reductive processes may not capture holistic experiences which require an empathic science that can understand and grasp the reality of transformations in social health. An empathic science such as Anthropology tends to be underpinned by triangulation whereby evidence from multiple sources converges and emerges as a single account. This paper based on camp observations as a Paediatrician for over ten years, interviews with staff and campers as adults in Europe and USA, and review of protocols and literature claims that the research approaches of Medical Anthropology can elucidate the experiential processes which underpin the social transformation of seriously ill children attending special holiday camps. Camp experiences are about erasing borderlines between the ill and the healthy. Borderlines have twin functions that can be explained by the single concept of liminality (Szakolczai, 2007): 'Both (functions) problematize the borderline, the limes : in one case it is ignored, in the other accentuated.' The borderline for children with life threatening illnesses is between two kingdoms whose distinctions are effectively ignored and erased in camp. The liminal experience of fun camps are part of a recognisable tripartite pattern of separation, transition and reintegration rituals summarised by vanGennep as a rite of passage. It enables children move from the kingdom of the sick to the kingdom of the well.